Design and Implementation of a Website-Based E-Commerce System for Digitalizing Agricultural Marketing and Empowering Local Farmers in Talawaan - Legi, Fabio Kevin Williams; Mongi, Charles Efraim; Ngangi, Stephano Caesar Wenston; Ketaren, Eliasta; Takaendengan, Mahardika Inra; Tenda, Edwin (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2025)
The present study focuses on the design and implementation of a website-based e-commerce information system for agricultural product marketing in Talawaan District. The research addresses the limited market access and digital marketing adoption among local farmers by developing a comprehensive e-commerce platform. The system's design employed the Rapid Application Development (RAD) methodology, undergoing iterative processes that encompassed requirements analysis, system design utilizing DFD and ERD, implementation, and Black Box Testing. The developed e-commerce system incorporates features such as product management capabilities, integrated payment methods, seller dashboards, and user-friendly interfaces tailored to farmers' technical capabilities. The findings indicate the efficacy of the system in digitalizing agricultural marketing processes, thereby empowering farmers to autonomously manage their products and expand their market reach without the need for intermediaries. The implementation has demonstrated positive impacts on farmers' digital literacy and product competitiveness. This research contributes to the digital transformation of agricultural marketing in rural areas and provides a replicable model for similar contexts